THE INFLUENCE OF COOPERATIVE LEARNING MODEL ON PROBLEM SOLVING ABILITY OF JUNIOR HIGH SCHOOL STUDENTS IN AL QURAN HADITH SUBJECT - Ibtisamah, Ghinaa; Haryono (STKIP Citra Bakti, 2026)
The study is intended to examine the impact of implementing the cooperative learning model with the Teams Games Tournament (TGT) approach on the problem-solving skills of junior high school students in the Al-Qur’an Hadith subject. This research uses a quantitative approach with a population of all class VII students at Mts. Fatahillah Semarang. This research uses a non-equivalent control group design for its quasi-experimental design. Data collection was carried out using observation, written assessments, and documentation techniques. The analysis revealed that the mean N-gain score of the control group was 9.15, whereas the experimental group obtained a higher mean score of 19.12. The normality test results indicated that the experimental group’s pretest score had a significance value of 0.169 and the posttest score 0.443, both exceeding 0.05, which confirms that the data were normally distributed. Furthermore, the homogeneity test produced a significance value of 0.095, greater than 0.05, indicating that the null hypothesis (Ho) was accepted and the variances of the two groups were homogeneous. Subsequently, hypothesis testing using the independent samples t-test resulted in a Sig. (2-tailed) value of 0.020, which is below the 0.05 threshold. Therefore, it can be concluded that a statistically significant difference exists between the problem-solving skills of students in the experimental class and those in the control class in the Al-Qur’an Hadith subject.